The Patterns of Practice and Outcomes of Penile Cancer in Ontario. Issue 4 (April 2017) - Mahmud, A.; Qu, X.; Yip, D.; Leveridge, M.; Mackillop, W.
Abstract: Aims: Penile cancer is a rare malignancy in Western countries. The management guidelines are mainly derived from retrospective studies as there are no randomised trials. The primary objective of this study was to assess patterns of practice and outcomes of penile squamous cell carcinoma in Ontario. Secondary objectives included examining trends in incidence, pathological characteristics and prognostic factors. Materials and methods: All patients diagnosed with penile cancer between 2000 and 2010 were identified from the Ontario Cancer Registry and all available pathology reports related to penile cancer during this period were reviewed. Results: Pathology reports of 419 new cases of penile squamous cell carcinoma were reviewed. There was a significant improvement in completeness of the pathology reports in recent years. The age-adjusted incidence was 0.9 per 100 000 person-years. Most patients presented with a pT1 lesion (63%). A partial penectomy (40%) was the most common surgical procedure. Over 38% of patients identified to be eligible for organ-sparing surgery had a total or partial penectomy. Only 23% of the eligible patients identified to require lymph node dissection underwent the procedure. The 5 year disease-specific survival for stage 0, I, II, III were 94%, 93%, 74% and 52%, respectively. Conclusions: There is a significant variation in the patterns of practice in Ontario. A large proportion of patients in this cohort were probably overtreated for the primary malignancy and undertreated for the regional nodes. Highlights: Largest population-based penile cancer study examining pathology reports. Local recurrence increases the risk of delayed nodal disease. Significant variation of practice in managing penile cancer in Ontario. Likely over- and/or undertreatment of varying clinical presentations. Suggest consideration of centralised management.